2004
DOI: 10.1080/09638280310001636419
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of health perspectives of those with physical disabilities: the role of spirituality as a determinant of health

Abstract: Although physical, social and psychological interventions are essential aspects of health intervention, by themselves they are not sufficient. Also required for health is a strong resilient self resulting from interaction and connection with other people and the natural world. Moreover, development of such an identity requires a spiritual world-view comprising an acknowledgement of the essence of self and focus upon the nature of the connection of this essence with all other aspects of life. Further research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Individuals who feel that their lives are meaningful and fulfilling may be motivated to comply with physicians' advice to engage in positive health behaviors [10,19]. The search for meaning and purpose in life within the context of illness and disability is challenging but potentially rewarding [38,39]. However, cardiac patients whose lives are meaningful may be more motivated to recover as much function as possible, and to transform cardiac illness into an opportunity for personal development.…”
Section: Discussionmentioning
confidence: 98%
“…Individuals who feel that their lives are meaningful and fulfilling may be motivated to comply with physicians' advice to engage in positive health behaviors [10,19]. The search for meaning and purpose in life within the context of illness and disability is challenging but potentially rewarding [38,39]. However, cardiac patients whose lives are meaningful may be more motivated to recover as much function as possible, and to transform cardiac illness into an opportunity for personal development.…”
Section: Discussionmentioning
confidence: 98%
“…There is empirical evidence that the meaning found through such existential turmoil predicts unique variance in higher self-esteem, and lower depression and anxiety (Wilt et al, 2021). There is evidence that self-esteem is one of the mediators of the positive effects of spirituality on well-being e.g., (Faull & Hills, 2004;Joshanloo & Daemi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interfaith spirituality seems to alleviate, in believers, existential anxieties that emerge with adversities and cumulative traumas' existential threats e.g., (Graham et al, 2001). A considerable body of literature provides consistent evidence of the positive correlation between existential interfaith spirituality (IFS) and self-reported, high quality of mental and emotional health e.g., (Exline & Rose, 2013;Faull et al, 2004;Pargament, 2013;Sawatzky et al, 2005). A meta-analysis (Smith-MacDonald et al, 2017) found that spirituality is associated with lower PTSD, in veterans.…”
Section: Interfaith Spirituality Circuit and Its Dynamicsmentioning
confidence: 99%
“…As it is achieved, physical and mental health become tools for realizing the purpose and meaning of life, which depicts the spiritual worldview. According to Faull et al [44], health requires a strong and stable "I" as a result of interaction and connection with other people and the natural world. Developing these needs requires a spiritual worldview that includes recognizing the essence of "I" and focusing attention on the nature of the connection with its essence and other life aspects.…”
Section: Factors Shaping the Spiritual Worldviewmentioning
confidence: 99%